Fluid flow at the Loppa High results from the seabed laboratory and test site - Chand, Shyam; Brunstad, Harald; Lepland, Aivo; Thorsnes, Terje; Pedersen, Jon Halvard (Frontiers in Earth Science, 2024)
1. The Loppa High is a subsurface structural high located in SW Barents Sea flanked by regional fault complexes where many hydrocarbon discoveries have been made along its peripheries during recent years. Since the petroleum exploration started in the late 1970’s, extensive studies have been undertaken giving a good understanding of the subsurface stratigraphy and the presence and maturation of hydrocarbon sources, fluid migration processes into hydrocarbon traps and seabed seeps. Many shallow gas anomalies are observed in this region due to fluid migration from the deeper reservoirs. Taking advantage of modern echo sounder and sonar technology, a more precise mapping of shallow subsurface became possible as well as detection of seafloor seeps to be inspected and sampled by advanced ROV technology. Presence of thermogenic hydrocarbons in seeps would indicate remobilisation from reservoirs in the subsurface that remained after the Late Paleogene/Neogene tectonism and the Pleistocene glacial rebound. Results of multibeam echosounder mapping of selected areas have been used to select seep sites for detailed investigation using ROV’s, and HUGIN AUV equipped with synthetic aperture sonar (HISAS), methane sniffers and optical cameras. This has aided the selection of optimal sampling sites and the collection of a large amount of sample material including seeping fluids, carbonate crusts and sediments which has been used for geochemical characterization and geochronology. Here, we present the evidence of the hydrocarbon migration and seepage from reservoirs mainly of deep thermogenic origin and altered by shallow storage during and after glaciation. The thermogenic signature of the seeping fluids indicates the long term and large-scale supply of methane to the global methane budget also from similar areas of potential natural leakage from the subsurface to the water column.